Relationship between schizophrenia and tobacco smoking - literature analysis - Magdalena Kozyra; Krystian Cholewa; Justyna Kaczerska; Natalia Śmiech; Joanna Milanowska (Journal of Education, Health and Sport, 2019)
Introduction: There is common statement, that schizophrenia patients are more likely to smoke comparing to the total world population. The aim of the study: The aim of this article is to find out why do schizophrenic patients smoke, how does it affect them and what can be the cause of susceptibility to smoking. Material and method: The research of the scientific articles was made on a database of PubMed and Google Scholar. Description of the state of knowledge: Many different associations were found during the research such as these describing that patients with schizophrenia have up to two to five times higher risk of developing type II diabetes. Also patients with diagnosed schizophrenia are characterized by low neuronal activity of the frontal and temporal lobes of the brain. In post mortem studies in schizophrenic patients a decrease in the number of M1 and M2 receptors in the brain was found, mainly in the dorsal lateral part of the prefrontal cortex, hippocampus, striatum and cingulate cortex, and decreased number of nicotinic receptors in the hippocampus, thalamus, cingulate cortex and prefrontal cortex The key process of undergoing of nicotine is the induction of the cytochrome P450 1A2 enzyme (CYP 1A2), thus increasing the metabolism of antipsychotic therapeutics, e.g. olanzapine, clozapine what explain why usage of nicotine is told to be self-treatment in schizophrenic people. Summary: This article gathers scientific research on the relationship between schizophrenia and susceptibility among patients to smoking addiction and its impact on both mental and physical health. However, not all mechanisms are known yet.